Bifidobacterium mellis sp. nov., isolated from the honey stomach of the honey bee Apis mellifera - Olofsson, Tobias C.; Modesto, Monica; Pascarelli, Stefano; Scarafile, Donatella; Mattarelli, Paola; Vasquez, Alejandra (International Journal of Systematic and Evolutionary Microbiology, 2023)
A novel Bifidobacterium strain, Bin7N T , was isolated from the honey stomach of the honey bee Apis mellifera . Cells are Gram-positive, non-motile, non-sporulating, facultative anaerobic and fructose 6-phosphate phosphoketolase-positive. Their optimal growth is at 37 °C in anaerobiosis in MRS (De Man, Rogosa and Sharpe) added with cysteine. The honey bee microbiota was composed of several phylotypes of Bifidobacterium and Lactobacillus . Comparative analysis of 16S rRNA gene sequence similarity revealed that strain Bin7N T grouped with Bifidobacterium species originating from honey bees and was closely related to Bifidobacterium asteroides DSM 20089 T (99.67 % similarity). However, the highest average nucleotide identity and digital DNA–DNA hybridization values of 94.88 and 60.6 %, respectively, were obtained with Bifidobacterium choladohabitans JCM 34586 T . The DNA G+C content of the type strain is 60.8 mol%. The cell-wall peptidoglycan is of the A4β l -Orn– d -Asp type. The main cellular fatty acids of strain Bin7N T are C 18 : 1 ω9 c , C 16 : 0 , C 18 : 1 ω7 c and C 18 : 0 . Phenotypic characterization and genotyping based on the genome sequences clearly show that this strain is distinct from the type strains of the so far recognized Bifidobacterium species. Thus, Bifidobacterium mellis sp. nov. (Bin7N T =DSM 29108 T =CCUG 66113 T ) is proposed as novel Bifidobacterium species.